Doxycycline Induced Pancreatitis: An Uncommon Complication of a Common Drug - William Reiche; Faith Abodunrin; Chris Destache; Rajani Rangray; Manasa Velagapudi (MDPI AG, 2022)
We describe the risk factors for the development, timing, and severity of doxycycline induced acute pancreatitis (DIAP) in two case reports and a review of prior published cases, to better understand DIAP. Clinicians must maintain a high level of suspicion for DIAP in patients presenting with acute pancreatitis, while on doxycycline therapy. The latency and severity of DIAP are variable, making diagnosis challenging. Treatment includes bowel rest, hydration, and discontinuation of doxycycline.